Bacteria Detection: From Powerful SERS to Its Advanced Compatible Techniques. Issue 23 (19th October 2020) - Zhou, Xia; Hu, Ziwei; Yang, Danting; Xie, Shouxia; Jiang, Zhengjin; Niessner, Reinhard; Haisch, Christoph; Zhou, Haibo; Sun, Pinghua
Abstract: The rapid, highly sensitive, and accurate detection of bacteria is the focus of various fields, especially food safety and public health. Surface‐enhanced Raman spectroscopy (SERS), with the advantages of being fast, sensitive, and nondestructive, can be used to directly obtain molecular fingerprint information, as well as for the on‐line qualitative analysis of multicomponent samples. It has therefore become an effective technique for bacterial detection. Within this progress report, advances in the detection of bacteria using SERS and other compatible techniques are discussed in order to summarize its development in recent years. First, the enhancement principle and mechanism of SERS technology are briefly overviewed. The second part is devoted to a label‐free strategy for the detection of bacterial cells and bacterial metabolites. In this section, important considerations that must be made to improve bacterial SERS signals are discussed. Then, the label‐based SERS strategy involves the design strategy of SERS tags, the immunomagnetic separation of SERS tags, and the capture of bacteria from solution and dye‐labeled SERS primers. In the third part, several novel SERS compatible technologies and applications in clinical and food safety are introduced. In the final part, the results achieved are summarized and future perspectives are proposed. Abstract : This progress report focuses on the progress for bacterial detection by surface‐enhanced Raman spectroscopy (SERS) and other compatible techniques, and the contents mainly include the following parts: the enhancement principle and mechanism of SERS, the progress of label‐free strategy and label‐based strategy for SERS detection of bacteria, several novel developed SERS compatible technologies and the application in clinical and food safety.